Quinolones for short-term treatment of uncomplicated urinary tract infection. (1999)
Objectives: To investigate whether quinolones produce in vivo responses comparable to reported in vitro activity against the spectrum of organisms in uncomplicated urinary tract infection (UTI) in Nigeria, Design: Equal numbers of patients with urine culture positive UTI were randomised to oral quinolone, pefloxacin 400 mg Bd and ofloxacin 200 mg Bd for 5 days. Setting: Out-patient clinics and wards at the University College Hospital. Ibadan. Subjects: Sixty patients aged sixteen years and above with uncomplicated UTI. Main outcome measures: Number of isolates, number of patients with clinical and bacteriological cure one week after commencing therapy. Relative effectiveness and side effects of the drugs. Results: Sixty four bacterial isolates were obtained with the enterobacteriaccae comprising 86%. 62 (97%) were sensitive to both drugs in vitro. Clinical cure occurred in 57 patients (95%), being 28 (93%) in those taking perfloxacin and 29 (97%) in those taking ofloxacin. Bacteriological cure occurred in 55 patients (92%), being 27 (90%) in those taking perfloxacin and 28 (93%) in those taking ofloxacin. 59 of the 64 isolates (92%) were eliminated week, 30 of 33 (91 %) in those taking pefloxacin, and 29 of 31 (94%) in those taking ofloxacin; the difference was insignificant (p=1.16). The enterobacteriaceae were generally susceptible to both drugs. Side effects were minor and infrequent. Conclusion: Quinolones were highly active against the common urinary pathogens in these Nigerian patients and can be reliably employed in treatment when culture results are unavailable.